2016
DOI: 10.1128/aem.03946-15
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glutathione Mediates Resistance to H 2 S Toxicity in Oral Streptococci

Abstract: Periodontal disease is associated with changes in the composition of the oral microflora, where health-associated oral streptococci decrease while Gram-negative anaerobes predominate in disease. A key feature of periodontal disease-associated anaerobes is their ability to produce hydrogen sulfide (H 2 S) abundantly as a by-product of anaerobic metabolism. So far, H 2 S has been reported to be either cytoprotective or cytotoxic by modulating bacterial antioxidant defense systems. Although oral anaerobes produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Generally, low concentrations (micromolar) of H 2 S are regarded as cytoprotective while high concentrations (millimolar) are cytotoxic (Ritter, 2010). Several studies have also established that H 2 S can either be cytoprotective or cytotoxic to microbes (Shatalin et al, 2011;Wu et al, 2015;Ooi and Tan, 2016;Fu et al, 2018). Shatalin et al (2011) showed that H 2 S is produced endogenously by orthologs of CBS, CSE, or MST in B. anthracis, P. aeruginosa, S. aureus, and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, low concentrations (micromolar) of H 2 S are regarded as cytoprotective while high concentrations (millimolar) are cytotoxic (Ritter, 2010). Several studies have also established that H 2 S can either be cytoprotective or cytotoxic to microbes (Shatalin et al, 2011;Wu et al, 2015;Ooi and Tan, 2016;Fu et al, 2018). Shatalin et al (2011) showed that H 2 S is produced endogenously by orthologs of CBS, CSE, or MST in B. anthracis, P. aeruginosa, S. aureus, and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to establish the generality of this adaptive response across a wider range of organisms. Others have posited that H 2 S-mediated cytoprotection occurs via sequestration of the prooxidant free Fe(II) (23,98); however, this remains incompletely understood.…”
Section: Physiological Conditions For the Production Regulation Andmentioning
confidence: 99%
“…Hydrogen sulfide has been shown to mediate several physiological effects in eukaryotic cells (30,31), including the promotion of glutathione production (32). In prokaryotic cells, it has been shown that reduced glutathione mediates resistance to H 2 S toxicity in oral streptococci (33). Hence, intracellular thiols are likely to be abundant in Kebrit's microorganisms.…”
Section: Resultsmentioning
confidence: 99%